1989
DOI: 10.1083/jcb.108.4.1317
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of the class I major histocompatibility antigen via a phorbol myristate acetate-inducible pathway is a cell-specific phenomenon and requires the cytoplasmic domain [published erratum appears in J Cell Biol 1989 Sep;109(3):1381]

Abstract: Abstract. Class I major histocompatibility (MHC) antigens are expressed by virtually all mammalian cells, yet their levels of expression and behavior on the cell surface vary in a cell-specific fashion. A panel of lymphoid (both B and T) and nonlymphoid cell lines was used to study the kinetics of internalization of the H-2L d class I MHC in different cell types. These studies revealed that endocytosis of H-2L J occurs by both constitutive and PMA-regulated pathways in lymphoid cells, but only by a PMA-refract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 78 publications
2
39
0
Order By: Relevance
“…Also, MHC-I molecules are known to be internalized, so the same model could apply to MHC-I. Since the rates of MHC-I internalization differ from cell type to cell type, it would be interesting to investigate how efficiently M153R downregulates MHC-I in different cell types (8). CD4 endocytosis is slowed down in the presence of the kinase Lck, which is present in T cells but not in HeLa cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Also, MHC-I molecules are known to be internalized, so the same model could apply to MHC-I. Since the rates of MHC-I internalization differ from cell type to cell type, it would be interesting to investigate how efficiently M153R downregulates MHC-I in different cell types (8). CD4 endocytosis is slowed down in the presence of the kinase Lck, which is present in T cells but not in HeLa cells (40).…”
Section: Discussionmentioning
confidence: 99%
“…Surface expression of MHC-I is also lost through internalization (20). Internalization of MHC-I occurs constitutively on activated lymphoid cells (23)(24)(25)(26)(27)). It appears that intact molecules are recycled to the cell surface and denatured molecules are shunted to a lysosomal pathway.…”
Section: Stability Ofmentioning
confidence: 99%
“…Endocytosis of MHC-I molecules has long been recognized, and occurs in a variety of different cell types (5)(6)(7)(8)(9). The process has biological implications for endosomal and lysosomal peptide loading and display, with the latter event designated as cross-presentation (14,33).…”
Section: Discussionmentioning
confidence: 99%
“…The rate of spontaneous endocytosis of MHC-I molecules is higher in lymphoid T cells and monocytes than in B cells and can be induced by activation of protein kinase C-regulated pathways (5)(6)(7)(8)(9). Zuniga and colleagues (5) were the first to report that endocytosis of MHC-I molecules required the cytoplasmic domain and suggested that a conformational change was required for endocytosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation